A non-convex equilibirum model when producers have many production alternatives - Rivera, Jorge (Estudios de Economía, 2016)
This paper is on general equilibrium theory, in finite dimensional spaces, where is considered explicitly the existence of exogenous parameters that may affect productivity of firms. Those parameters could be associated with external restriction or possibilities to produce as, for instance, size of the firm or technical options to adopt. In the model will be assumed that for each firm these parameters that defines technology of production are a decision variable for firms, which generalizes the standard model where technology is fixed a priory. The main result of the paper is the existence of equilibrium theorem under general assumptions over the economy, in particular the presence of non-convexities in production.